Effects of training on employees performance of construction firms in Pahang - Muhd Nur Hakimi, Mazlan (2016)
This study is about the effect of training on employees performance of construction firms in Pahang. This study begins with the realization about the effect of training on employee’s performance. Employees role actually influence the success of an organizations. No matter what the role of the worker whether project manager, site supervisor, labour, or subordinates all are contribute and play important role in developing organization and also increasing the organizational productivity. In general, the training seeks to improve the quality of the performance in their jobs. Training has been accepted as a factor that contributes to the achievement of organizational goals. The scope of this study is among employees whose work at construction industry in Pahang especially in Kuantan. The total sample of 57 respondents out of 70 of construction companies were used in this study. For the result of this study has been identified that there are significant relationship between training and employees performance.